Production, purification and biochemical characterisation of a novel lipase from a newly identified lipolytic bacterium Staphylococcus caprae NCU S6 - Junxin Zhao; Maomao Ma; Zheling Zeng; Ping Yu; Deming Gong; Shuguang Deng (Taylor & Francis Group, 2021)
A novel lipase, SCNL, was isolated from Staphylococcus caprae NCU S6 strain in the study. The lipase was purified to homogeneity with a yield of 6.13% and specific activity of 502.76 U/mg, and its molecular weight was determined to be approximately 87 kDa. SCNL maintained above 80% of its initial activity at a wide range of temperatures (20-50 °C) and pH values (6-11), with an optimal temperature at 40 °C and optimal pH at 9.0 with p-nitrophenyl palmitate as a substrate. SCNL exhibited a higher residual activity than the other staphylococcal lipases in the presence of common enzyme inhibitors and commercial detergents. The lipase activity was enhanced by organic solvents (isooctane, glycerol, DMSO and methanol) and metal ions (Na+, Ba2+, Ca2+, and Mn2+). The Km and Vmax values of SCNL were 0.695 mM and 262.66 s−1 mM−1, respectively. The enzyme showed a preference for p-NP stearate, tributyrin and canola oil. These biochemical features of SCNL suggested that it may be an excellent novel lipase candidate for industrial and biotechnological applications.